What Drives the Jakarta Islamic Index? Evidence from Inflation, Exchange Rates, and Global Oil Prices - Khusnul Lailia; Anton Bawono; Rina Rosia (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the effects of inflation, exchange rates, and global oil prices on the Jakarta Islamic Index (JII) in Indonesia. The approach used in this study is a quantitative approach utilizing secondary time-series data for the period 2016–2025, consisting of 120 monthly observations. The analytical technique used was multiple linear regression, with first-difference transformation to address the issue of data nonstationarity. The results indicate that inflation does not have a significant effect on the JII. Conversely, the exchange rate was found to have a significant negative effect, suggesting that a depreciation of the rupiah tends to dampen the performance of the Islamic stock index. Meanwhile, global oil prices have a significant positive effect on the JII. Collectively, these three variables account for 29,34% of the variation in the JII. These findings are expected to serve as a useful reference for investors and stakeholders in understanding the dynamics of macroeconomic factors in the Islamic capital market.